Connectors for electrical and electronic equipment. Detail specification for up to 7 ways including PE or FE (data/power) and shield pin, free and fixed circular connectors for balanced single-pair data transmission with current-carrying capacity. Mechanical mating information, pin assignment and additional requirements for type 7 Part 7, (7th June 2023) - British Standards Institution,
No abstract available